Time-varying risk of death after SARS-CoV-2 infection in Swedish long-term care facility residents: a matched cohort study. Issue 11 (24th November 2022) - Ballin, Marcel; Ioannidis, John P; Bergman, Jonathan; Kivipelto, Miia; Nordström, Anna; Nordström, Peter
Abstract : Objectives: To evaluate whether SARS-CoV-2 infection in residents of long-term care (LTC) facilities is associated with higher mortality after the acute phase of infection, and to estimate survival in uninfected residents. Design: Extended follow-up of a previous, propensity score-matched, retrospective cohort study based on the Swedish Senior Alert register. Setting: LTC facilities in Sweden. Participants: n=3604 LTC residents with documented SARS-CoV-2 until 15 September 2020 matched to 3604 uninfected controls using time-dependent propensity scores on age, sex, health status, comorbidities, prescription medications, geographical region and Senior Alert registration time. In a secondary analysis (n=3731 in each group), geographical region and Senior Alert registration time were not matched for in order to increase the follow-up time in controls and allow for an estimation of median survival. Primary outcome measures: All-cause mortality until 24 October 2020, tracked using the National Cause of Death Register. Results: Median age was 87 years and 65% were women. Excess mortality peaked at 5 days after documented SARS-CoV-2-infection (HR 21.5, 95% CI 15.9 to 29.2), after which excess mortality decreased. From the second month onwards, mortality rate became lower in infected residents than controls. The HR for death during days 61–210 of follow-up was 0.76 (95% CI 0.62 to 0.93). The median survival of uninfected controls was 1.6 years, which was much lower than the national life expectancy in Sweden at age 87 (5.05 years in men, 6.07 years in women). Conclusions: The risk of death after SARS-CoV-2 infection in LTC residents peaked after 5 days and decreased after 2 months, probably because the frailest residents died during the acute phase, leaving healthier residents remaining. The limited life expectancy in this population suggests that LTC resident status should be accounted for when estimating years of life lost due to COVID-19.